Obtaining funds on the basis of leasing in the Republic of Srpska - Lošić Slavko; Malinović Mirko; Jovanović Milica (Ekonomski Signali, 2020)
This paper is dedicated to leasing operations in the Republic of Srpska, which are regulated by law. Leasing is a legal transaction where the lessor transfers the right to hold and use the leased object to the lessee for a certain period, with his obligation to pay the agreed leasing fee and with the right to return the leased object to the lessor, buy it or extend the lease agreement. This way of financing is mostly used by newly established, small and medium enterprises, which do not already have the amount of funds needed to obtain investment goods. By concluding a leasing contract, the lessee does not acquire the right of ownership over the object of leasing, but acquires economic benefits from the use of the object of leasing. The lease agreement usually coincides in time with the useful life of the assets, i.e. the period of depreciation calculation. The practice is that the same contract allows the lessee to repurchase the leased asset at a symbolic price.